Program Peningkatan Aset PAUD Seroja dengan Mengembangkan Fasilitas Pembelajaran Berkualitas Pada Anak Usia Dini Berbasis Web - Haryati; Untung Surapati; Muhammad Aqil Septiansyah; Tracy Olivera Lingga (Jurnal Pengabdian Nasional (JPN) Indonesia, 2024)
This research aims to improve early childhood learning facilities at PAUD Seroja through the implementation of web applications as part of community service activities. The success of this research can be seen through the effectiveness of the application in managing inventory data, teacher information, and student information. The proposed improvement suggestions include regular updates, increasing the level of security, as well as developing additional features such as payment system integration, as concrete steps in optimizing this service activity. The application implementation process involves active participation from users, who are also stakeholders in service activities. The main hope is that this application will not only increase the efficiency of information management at PAUD Seroja but also make a positive contribution to the experience and quality of early childhood learning. Recommendations and input from users will be the main basis for continuous improvement and further development, which is under the spirit of community service activities. This research contributes to efforts to develop early childhood education by utilizing information technology, as well as confirming the role of service activities as a means of optimizing the use of technology in improving the quality of learning at PAUD Seroja.